JSE Delisted Companies' Use of Impression Management Practices in the Chairman’s Statement and Audit Committee Report Preceding Delisting from the 2016-2021 Period - PHESA, Masibulele; SIBANDA, Mabutho; GUMEDE, Zamanguni Hariatah (International Journal of Environmental, Sustainability, and Social Science, 2023)
The study examined whether Johannesburg Stock Exchange (JSE Ltd) delisted companies used impression management in the chairman’s statements and audit committee's reports preceding delisting from 2016 to 2021. There is a concerning trend of delisting from JSE, which may be voluntary or compulsory. The chairman’s statement is highly ranked as the most read voluntary narrative disclosure statement. Furthermore, as assurance providers and governance structure, the audit committee is expected to assure the organisation as a whole. The study uses quantitative content analysis on integrated reports of the JSE-delisted companies from 2016 to 2021. Impression management is examined for length, use of passive voice, and the use of personal references in the chairman’s statement and audit committee report. The study examined and provided insight into impression management practices used by delisted companies and ascertains whether there is a systematic difference in the use of impression management between profitable and unprofitable in the year preceding delisting. The study shows that delisted companies used impression management on the verge of delisting and this opportunistic behavior was used by both boards of directors and audit committees. This study contributes to the novelty of knowledge on impression management. It is the first of its kind.